Czek i jego forma w projekcie ustawy czekowej z 1923 roku - Górnicki, Leonard (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In this article, I deal with the fundamental issues regarding cheques and their form in the first draft of the law of cheques, which was drawn up by Stanisław Wróblewski, prepared by the Codification Committee and published with its motives in 1923. The draft law did not assume the full emancipation of the material cheque law and subjected the cheque to the specified scope of legal regulation provided for in the promissory note. On the other hand, it emphasized formal emancipation: 1 exclusion of the cheque institution, as well as the promissory note, from general civil law, and consequently subjecting them to special regulation; as well as 2 separating the matter of cheques from the promissory notes, that is the development of a cheque act separate from the promissory note act.As regards the form of cheques, the draft law relied on art. 1–7 of the Hague resolutions of 1912. The Polish codifiers departed from this model, especially when it was required by the economic conditions of Poland, taking special care to prevent situations that could discredit cheques at the beginning of their development. Therefore, they did not accept in particular the solution proposed in the Hague resolutions Article 5, which did not accept the scriber’s capacity as the condition of cheque validity.
Keywords: kodyfikacja prawa czekowego; rezolucje haskie w zakresie prawa czekowego z 1912 roku; projekt prawa czekowego z 1923 roku; forma czeku; klauzula czekowa; zlecenie zapłaty; bierna zdolność czekowa